KEPEMIMPINAN DALAM ORGANISASI DI ERA DUNIA VIRTUAL - Imam Hidayah; Fajar Harits Santoso; Ayu Sulistya Putri Sugeng (Institut Bisnis Muhammadiyah Bekasi, 2023)
Abstract Pandemic has resulted many changes, Virtual world had become massively growing.Every aspects of life become more virtual and less physical. Most of organizations and company are having no different in phasing virtual era, they have to be moved their working space from the office to from home or even from everywhere. A team coordination and leadership inside it, is also shifted to be more challenging because of less physical meeting. The authors try to elaborates about leadership in virtual world era, when every physical meeting is limited. Is there any different from the previous era? And is there any certain expectations of the employees about their leader. Qualitative method through several times deep interview towards five interviewees is being used by the writers to get a picture towards the specific issue related on leadership in virtual era. After collecting the data, the writer will give an explanative description about the interview results. In this article, the author found transformational theories aspect such as idealist influence, motivational inspiration, intellectual stimulation and individual consideration are needed for some employees to enhance their quality of work. Keyword: Leadership; Organizations; Communication; Virtual World; Work from Home (WFH)